Understanding scoping reviews: Definition, purpose, and process. Issue 1 (1st June 2016) - Peterson, Jessica; Pearce, Patricia F.; Ferguson, Laurie Anne; Langford, Cynthia A.
Abstract: Background/purpose: Scoping review design represents a methodology that allows assessment of emerging evidence, as well as a first step in research development. Despite its increasing use, to date no article reflecting use of scoping review methodology has been submitted for review at JAANP . The purpose of this article is to provide detailed information on scoping reviews, including definition, related processes, and uses, and discuss the relationship to nurse practitioner (NP) practice, policy, education, and research. The longer‐term goal is that NPs will understand the related techniques, consider the methodology as a viable one for NP scholarship, and bring related reports to the forefront of NP publications. Methods: This manuscript represents a brief report. Processes to develop the brief include detailed search and review of scoping review literature in CINAHL and PubMed. Both methodologic reports and reviews were included. Definitions and uses of scoping reviews were reviewed. Conclusion: The definition and process of scoping review are evolving. Although there is controversy regarding the methodology, there is increasing visibility of scoping review methodology in the published literature since the year 2000, with over 500 published reviews currently available. Implications for practice: A well‐executed scoping review has potential to inform NP practice, policy, education, and research.